Strategic Management Overview: A Key to Success in the Corporate Sector - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
It is very important to understand the current situation and the types of challenges the business will encounter from the existing environment to assess the mission and the priorities of an organization. The company will carry out its mission and goals by effective use of strategies. The companies should therefore be aware of strategic management and planning. Strategic planing, that requires much strategic thought, is one of the most important management instruments that helps managers identify priorities and identify key actions needed to accomplish the organization’s tasks and goals. In the present day’s complex business environment, strategic management is one of the main topics in organizational management. This paper incorporates the principles of policy, strategic planning, strategic thinking and strategic management. It’s very important to understand the current situation and the types of challenges that the business will encounter from the existing environment in order to assess the purpose and goals of an organisation. The organization can achieve its task and goals by successfully deploying strategies. The organizations should therefore be mindful of financial and strategic planning. Long term planning, one of the most effective management tools, requires a lot of strategic thinking, which allows managers to define goals and determine the major actions required to achieve the organization’s objectives and tasks.Strategic management has now become one of the main topics of corporate management due to the complex business environment. The paper addresses strategic principles, action planning, strategic analysis, strategic management as well as the importance of strategic management.The comparison between Eastern and Western corporations also helped to understand the role of culture and environment in the development of the corporate strategy.